Exploration of the Application of Islamic Management Principles in the Management of Construction Businesses - Musmuliadi Kamaruding; Mohd Syahmir Alias; Abang Mohd Razif Abang Muis; Mohamad Zulfakhairi Mokthar (HRMARS, 2023)
This article explores the concept of Islamic management and its application in the context of construction business management (CBM). Islamic management is a comprehensive approach that integrates Islamic principles into organizational and business practices, emphasizing values such as integrity, fairness, social responsibility, and excellence. The article highlights the importance of holistic CBM, which considers project management and strategic planning, marketing, human resource management, and risk management. Drawing inspiration from the Qur’an and the Sunnah, Islamic management principles are grounded in justice, accountability, and responsibility toward all stakeholders. The article discusses the key principles of Islamic management, including sincere intentions, fair profit distribution, strong customer relationships, social responsibility, worker safety and welfare, cleanliness and aesthetics, the balance between worldly and spiritual pursuits, and the pursuit of excellence. It demonstrates how these principles can be applied in CBM to promote ethical practices, sustainability, and long-term success. By incorporating Islamic management principles, construction businesses can operate according to Islamic teachings, foster ethical decision-making, and contribute to a socially conscious and environmentally responsible construction industry.